Multispectral Polarization State Analyzer of Scanning Polarimeter ScanPol. (26th October 2020) - Syniavskyi, Ivan; Oberemok, Yevgen; Ivanov, Yuriy; Sosonkin, Mikhail
Abstract : We present the results of the development of a representational model of the multispectral polarization state analyzer of the ScanPol scanning polarimeter for the space experiment Aerosol-UA. The aim of the Ukrainian space mission Aerosol-UA is to create a database based on continuous satellite measurements of the optical characteristics of aerosol and cloud particles in the Earth's atmosphere over a long period of time. The ScanPol polarimeter is designed to acquire spatial, temporal, and spectral-polarimetric measurements simultaneously to minimize instrumental "parasitic" effects and effects of "false" polarizations due to scene movement. Simultaneity is provided by separation of the initial spatial field by a pair of conjugated telescopes and a pair of Wollaston prisms. ScanPol provides to measure the first three Stokes parameters I, Q, and U of the radiation reflected by atmospheric aerosols and the Earth's surface for a six solar reflectance spectral bands in the near ultraviolet (NUV), visible (VIS), and near-infrared (NIR) spectral channels centered in the wavelengths 370 nm, 410 nm, 555 nm, 865 nm, 1378 nm, and 1620 nm. Stokes parameters I, Q, and U are used to determine a degree of linear polarization of radiation that will allow obtaining the phase function and polarization characteristics of aerosol particle scattering, estimate their size, and determine the aerosol type and optical thickness. The polarimeter optical layout is considered, and the spectral characteristics of the transmission of optical channels are given. Obtained signal-to-noise ratio exceeded 500 for wavelengths 370 nm and 410 nm and exceeded 1000 for other wavelengths. The design of the chosen photodetectors is based on surface mount type photodiodes: Si-photodiodes Hamamatsu S10356-01 for the optical range of 370–860 nm and InGaAs-photodiodes Hamamatsu G8941-011620 for wavelengths 1378 nm and 1620 nm. The effect of orientation of Wollaston prisms axes on polarization measurement error is considered. The errors of azimuth mount of Wollaston prisms ≤2 arcmin in ScanPol leads to error of degree of linear polarization ≤0.0012.